2022
DOI: 10.21608/tsnj.2022.253966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Design Nursing Instruction on Mechanically Ventilated Children in Pediatric Intensive Care Units

Abstract: Background: Mechanical ventilation is one of the most devices that are indispensable to use in Pediatric Intensive Care Units. However, all over the world many children are dying in Pediatric Intensive Care Units. Mechanical ventilation is help and supports management in the Intensive Care Unit, but it may cause a lot of threats and complications. This study aimed to evaluate the effect of a design nursing instruction on mechanically ventilated children in pediatric intensive care units. Methods: Research desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The finding was confirmed by Mahfoz et al (2022) who reported that there were statistical significance variances among the nurses' practice of chest physiotherapy during pre and post-test of nursing care provided for children with mechanical ventilation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The finding was confirmed by Mahfoz et al (2022) who reported that there were statistical significance variances among the nurses' practice of chest physiotherapy during pre and post-test of nursing care provided for children with mechanical ventilation.…”
Section: Discussionmentioning
confidence: 69%
“…In the same line, Mahfoz, El Sayed, and Ahmed (2022), who found that there were statistically significant differences related to nurses' practice about hand washing in the pre and post program implementation, which all the nurses completely done hand washing after implementing the instruction. This situation is identical to that described by Ismail and Zahran (2015), which reported that nurses realized the importance of hand washing as a VAP prevention intervention and saw notable changes in nurses' hand washing behaviors quickly after putting the program's instructions into effect.…”
Section: Discussionmentioning
confidence: 84%
“…The current study result was supported by Amin, Samra, and Lawend (2021) whose found in their study that, there were significant improvement in knowledge about risk factors of VAP through all program phases. On contrary with Mahfoz, El Sayed, and Ahmed (2022), who found that half of the studied nurses replied the correct answer regarding risk factors of VAP.…”
Section: Discussionmentioning
confidence: 77%
“…Konstipasi pada lansia dengan komplikasi enteral selain membantu melancarkan buang air besar, dapat mengurangi distensi abdomen (Çetinkaya et al, 2020). Hasil penelitian ini sesuai dengan penelitian yang dilakukan (Mohamed et al, 2021) dan (Younis et al, 2023) pada pasien yang dirawat di intensive care unit. Pijat abdomen dapat merangsang aktivitas parasimpatis sehingga meningkatkan fungsi saluran cerna.…”
Section: Pembahasanunclassified